1989
DOI: 10.1104/pp.91.4.1609
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation and Distribution of Peroxidase Isoenzymes in the Cucurbitaceae

Abstract: Ethylene enhanced the levels of peroxidases in the roots, stems, leaves, and cotyledons of 2-week-old cucumber Cucumis sativus cv Poinsett 76 seedlings. Antibodies to the isoelectric point (pi) 9 and pi 4 isoenzymes were used in a radial immunodiffusion assay to demonstrate that ethylene induced similar peroxidases in other cultivars of C. sativus, other species of Cucumis and other genera of Cucurbitaceae. Examination of ethylene-induced peroxidases, using isoelectric focusing gels, demonstrated the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…This is consistent with earlier work showing that ethylene increased the levels of pI 4 and pI 9 peroxidase in cotyledonary tissue ( 1). Plants have a number of peroxidase isozymes.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with earlier work showing that ethylene increased the levels of pI 4 and pI 9 peroxidase in cotyledonary tissue ( 1). Plants have a number of peroxidase isozymes.…”
Section: Discussionsupporting
confidence: 93%
“…Now it can be easily detected that the case of stress POD is very similar to that of stress ethylene. More interestingly, there are publications reporting that both ethylene and POD can stimulate each other (Abeles et al, 1989;Gasper et al, 1985;Osswald et al, 1989).…”
Section: Soluble Pod Activity (%) 120mentioning
confidence: 99%
“…These phenomena are often accompanied by an increase POD activity (Kim et al 2000;De and De 2003). Ethylene has been shown to increase POD activity in sweet potato, cucumber, pea, tomato, and tobacco and also to affect mRNA expression of POD in suspension cultured cells of peanut (Abeles et al 1989;Kim et al 2000). Kar and Mishra (1976) have indicated that in rice leaves, POD and PPO activity were increased with the progress of senescence while CAT activity decreased.…”
Section: Resultsmentioning
confidence: 96%
“…Detoxification of H 2 O 2 is mediated by catalase localized in peroxisomes (Weckx and Clisters 1997;Nandwal et al 2000). It has been reported that ethylene (100 ll/l) enhanced the activity of acidic, neutral and basic peroxidases in Cucumis sativus seedlings (Abeles et al 1989). Stimulation of ethylene synthesis has been reported resulting in the generation of reactive oxygen species (Wang et al 2002).…”
Section: Introductionmentioning
confidence: 98%